Synthesis of a Two-Dimensional Molybdenum Disulfide Nanosheet and Ultrasensitive Trapping of Staphylococcus Aureus for Enhanced Photothermal and Antibacterial Wound-Healing Therapy - Weiwei Zhang; Zhao Kuang; Ping Song; Wanzhen Li; Lin Gui; Chuchu Tang; Yugui Tao; Fei Ge; Longbao Zhu (Nanomaterials, 2022)
Photothermal therapy has been widely used in the treatment of bacterial infections. However, the short photothermal effective radius of conventional nano-photothermal agents makes it difficult to achieve effective photothermal antibacterial activity. Therefore, improving composite targeting can significantly inhibit bacterial growth. We inhibited the growth of Staphylococcus aureus (S. aureus) by using an extremely low concentration of vancomycin (Van) and applied photothermal therapy with molybdenum disulfide (MoS2). This simple method used chitosan (CS) to synthesize fluorescein 5(6)-isothiocyanate (FITC)-labeled and Van-loaded MoS2-nanosheet hydrogels (MoS2-Van-FITC@CS). After modifying the surface, an extremely low concentration of Van could inhibit bacterial growth by trapping bacteria synergistically with the photothermal effects of MoS2, while FITC labeled bacteria and chitosan hydrogels promoted wound healing. The results showed that MoS2-Van-FITC@CS nanosheets had a thickness of approximately 30 nm, indicating the successful synthesis of the nanosheets. The vitro antibacterial results showed that MoS2-Van-FITC with near-infrared irradiation significantly inhibited S. aureus growth, reaching an inhibition rate of 94.5% at nanoparticle concentrations of up to 100 µg/mL. Furthermore, MoS2-Van-FITC@CS could exert a healing effect on wounds in mice. Our results demonstrate that MoS2-Van-FITC@CS is biocompatible and can be used as a wound-healing agent.